Elements of Human Psychology in Robert Frost’s Poem “The Road Not Taken”: A Literary Analysis - Khurram, Shagufta; Chachar, Zulfiquar Ali; Qadri, Farhana Yasmeen (Pakistan Languages and Humanities Review, 2024)
The study concentrates on various psychological theories and notions, such as judgment, regret, introspection, and personal development. An American poet, Robert Frost (1874–1963), wrote "The Road Not Taken," a well-known poem first published in 1915. Because of its distinct perspectives and dimensions, "The Road Not Taken" is significant in American literature. This study adopts a qualitative research methodology, with literary analysis as the primary way to gather data. The poem "The Road Not Taken" by Robert Frost served as the study’s primary data source. In the current study, the researcher has examined the psychological foundations of the poem. We can learn more about the psychological aspects of "The Road Not Taken" and how choices are made and handled by developing an excellent grasp of the human experience. The conclusions drawn from this approach can be used in several disciplines, such as psychology, literature, and philosophy. The study’s findings support several recommendations that can be made to improve the comprehension and application of psychological principles in literary analysis, decision-making processes, and interdisciplinary studies. These recommendations include the use of scholarly works in psychological therapy, educational and curriculum development, and the integration of psychological theories in literary studies.